Design Failure Affecting Maintenance Management on Public Higher Education Institution in Malaysia - Aras Agus Salim, Nuzaihan; Muhamad Salleh, Naziah; Zahari, Nurul Fadzila (EDP Sciences, 2016)
The issue of government building defect is keeping on reporting in the media and arising since 2007. These issues of building defects, maintenance and management have existing and it is deliberated up to the parliament level. The government keep continue increased the maintenance allowance in National Budgetary in every year. However, the building disasters and failures keep going develop their number of cases in Malaysia. Most of the issues are related with a weak maintenance management and faulty in design. This reflects to a poorly building condition, create discomfort and danger environment to the building users. Besides, it will result to a low quality building condition and reflect to a weak building maintenance management. Building defects arise through inappropriate or poor design, specification, construction and it will give an impact to maintenance management itself [1]. Errors in the design of the building are being debated and becoming a reason of major factor in building defect reproduction [2]. Thus, this issue will discover the major cause in building design failure that develop the building defects and verify the impact of design defects towards building maintenance management. The study involved with the public higher education institution in Malaysia focusing on main campuses and the distribution of questionnaire to the facility and maintenance management department. This research is aimed to produce a better understanding on the impact of building design failure towards the institution facilities’ condition.